1989
DOI: 10.1530/jrf.0.0870401
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin can induce year-round ovarian cyclicity in red deer (Cervus elaphus)

Abstract: ). Plasma prolactin concentrations remained suppressed ( < 20 ng/ml) for the duration of melatonin-feeding (Groups CL/M and NL/M) whereas control values (Group C) were elevated (20\p=n-\120ng/ml) between April and August (P < 0\m=.\05).The ovarian response by hinds to melatonin therefore depends on initial reproductive status and recent photoperiodic history, and continued administration to cyclic hinds stimulates prolonged ovarian cyclicity irrespective of the time of year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…The ability of melatonin implants, inserted at the spring equinox, to prevent seasonal anoestrus provides further support for the contention that the duration of the daily photoperiod is the primary determinant of this reproductive seasonality. Melatonin implants, inserted at or soon after the spring equinox, prevented the occurrence of seasonal anoestrus and maintained continuous oestrous cycles for the duration of the study, just as daily oral administration of melatonin at 15:00 h throughout the summer does in red deer hinds (Adam et al, 1989). This finding is in contrast to the situation in sheep, in which prolonged maintenance of a short-day photoperiod after the winter solstice, or its simulation by melatonin implants, fails to prolong the breeding season significantly (Malpaux et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of melatonin implants, inserted at the spring equinox, to prevent seasonal anoestrus provides further support for the contention that the duration of the daily photoperiod is the primary determinant of this reproductive seasonality. Melatonin implants, inserted at or soon after the spring equinox, prevented the occurrence of seasonal anoestrus and maintained continuous oestrous cycles for the duration of the study, just as daily oral administration of melatonin at 15:00 h throughout the summer does in red deer hinds (Adam et al, 1989). This finding is in contrast to the situation in sheep, in which prolonged maintenance of a short-day photoperiod after the winter solstice, or its simulation by melatonin implants, fails to prolong the breeding season significantly (Malpaux et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…These results show clearly that oral application of melatonin to extend the period each day when plasma melatonin is increased, thus mimicking the natural endogenous diurnal rhythm typical of short days, overcomes the inhibition of puberty, but that the provision of a constant-release implant does not. In this, domestic pigs differ from sheep and deer, in which both implants and oral melatonin can stimulate reproductive activity under inhibitory photoperiods (Kennaway et al, 1982;Lincoln & Ebling, 1985;Adam & Atkinson, 1984;English et al, 1986;Adam et al, 1989). We have previously shown that constant-release melatonin implants given by the same regimen as used in Expt 1 provide a constant, high plasma melatonin concentration above which a diurnal rhythm cannot be detected (Paterson et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In sheep (Kennaway et al, 1982;Lincoln & Ebling, 1985;English et al, 1986), deer (Adam & Atkinson, 1984;Adam et al, 1989;Fisher et al, 1989) and goats (McGregor et al, 1989) inhibition of reproductive activity by long days can be overcome by the administration of exogenous melato¬ nin, given either orally or by slow-release implant. We have already demonstrated that the seasonal inhibition of attainment of puberty in domestic gilts can be prevented by applying a short-day regimen (Paterson & Pearce, 1990), but such methods may be difficult to use in combating seasonal reproductive dysfunctions at the practical level.…”
Section: Introductionmentioning
confidence: 99%
“…Further support for this hypothesis comes from experiments where hinds have been treated with melatonin for over a year, commencing in late winter before they had entered anoestrus. Prolactin concentrations remained suppressed and hinds continued to show repeated oestrous cycles throughout the entire treatment period (Adam et al 1989). In addition to the effects on prolactin, treatment with either drug is likely to have direct effects on the secretion of other pituitary hormones.…”
Section: Role Of Prolactin In Species With Photoperiodic Inhibition Omentioning
confidence: 99%